The Application of Electron Microprobe Dating Method on a Genetic Type of Uraninite - Zhao huibo; Liu yafei; Yang shan; Ye meifang; Wang zhihai; Wang bo; Chang na (Yankuang ceshi, 2014)
Based on the advantages of high resolution and accuracy, Electron Probe Microanalysis (EPMA) method for Th-U-Pb is conducted to date monazite and zircon, is not typically applied in uraninite, pitchblende and other minerals which contain high contents of Th, U and Pb. Uraninite with a high content of U was first found in the iron deposit, whose rock type was chlorite and actinolite biotite altered rock. Based on the region′s geological background, the microscopic alteration, age calculation and other related elements analysis, the uraninite mineralization age and metallogenic regularity have been studied intensely by Microscope and EPMA. The research results indicate that the genetic type of uraninite is similar to the famous metamorphic uraninite in Australia, belonging to the old metamorphic type. The gangue minerals are all chlorite altered by biotite. Occurrence characteristics of the uraninite reveal the close relationship between uraninote and biotite-chlorite. The mineralization age is also intimately related to the formation age of biotite and chlorite. According to the oxide content data of elements (U, Th and Pb) by EPMA, mineralized periods were obtained as the main mineralization stage is (1654±17) Ma-(1805±17) Ma, which is the mid Proterozoic and relate to the hydrothermal alteration of biotite. The later activation and enrichment period is (657±17) Ma-(807±17) Ma, which is the Neoproterozoic Nanhua period when hydrotherm invaded and chloritization was widely developed. Large-sized uraninite grains were selected to calculate their zoning ages. The age distribution shows that the strong fluid activity occurs at the late stage, and is mainly related to the chloritization. In addition, comparing the elements′ content (Y2O3 and UO2) between metamorphic uranium and sedimentary uranium, a negative correlation relationship was found between the two types. This relationship may have significance in determining whether it is metamorphic or sedimentary type, but this conclusion needs further study due to the lack of convincing evidence.